Expected Devaluation and Economic Fundamentals - Thomas, Alun (IMF Working Papers; Working Paper ;, 1993)
Recent incidents of exchange rate collapse have provoked interest in the extent to which such events are determined by economic fundamentals. This paper considers whether interest rate differentials are appropriate measures of the risk of devaluation and whether this measure of devaluation risk reflects the movements of variables which capture internal and external balance. The paper finds that interest rate differentials reflect devaluation risk but that movements in fundamental variables have only a weak effect on devaluation risk in France and Italy. The most significant influence on devaluation risk is the position of the currency in its band in that the lower is the exchange value of a currency within the band, the greater is the perceived risk of devaluation.